Retrospective Cohort Study of the Efficacy of Azithromycin Vs. Doxycycline as Part of Combination Therapy in Non-Intensive Care Unit Veterans Hospitalized with Community-Acquired Pneumonia. (4th October 2017) - Spivey, Justin; Sirek, Heather; Wood, Robert; Devani, Kalpit; Brooks, Billy; Moorman, Jonathan
Abstract: Background: The IDSA Community-Acquired Pneumonia (CAP) Guideline recommends ceftriaxone in combination with doxycycline as an alternative to combination therapy with ceftriaxone and azithromycin for non-intensive care unit (ICU) patients hospitalized with CAP. This is an attractive alternative regimen due to recent concerns of increased cardiovascular risk associated with azithromycin. The objective of this study was to compare the clinical outcomes of azithromycin and doxycycline each in combination with ceftriaxone for non-ICU Veterans hospitalized with CAP. Methods: This retrospective cohort study included Veterans with pneumonia admitted to the VA MidSouth Healthcare Network from January 2007 to January 2015 who received ceftriaxone plus either azithromycin or doxycycline within 48 hours of admission. Demographics, modified CURB-65, Charleston Comorbidity Index (CCI), antimicrobials received, and microbiology data were obtained. A composite outcome was used to assess clinical failure and included either broadened antimicrobial coverage during index hospitalization, mortality, readmission, or emergency department visit within 30 days. Univariate and multivariate logistic regression were performed to identify risk factors associated with clinical outcomes. Results: 3788 patients met inclusion criteria: 3711 in the azithromycin group and 77 in the doxycycline group. These were well-matched according to CAP severity and comorbidities. There was no statistical difference in the composite outcome between the azithromycin and doxycycline groups (44.3% vs 51.9%, P = 0.18). Multivariate analysis identified positive blood culture (OR 5.81, 95% CI 2.69–12.55), CURB-65 [2 vs 0] (OR 1.24, 95% CI 1.05–1.47), CURB-65 [≥3 vs 0] (OR 2.4, 95% CI 1.22–4.71) and CCI (OR 1.1, 95% CI 1.06–1.14) as risk factors for the composite outcome. Receipt of doxycycline was not associated with components of the composite outcome in secondary analyses. Conclusion: Doxycycline was not associated with a statistical difference in the composite outcome for non-ICU Veterans hospitalized for CAP compared with azithromycin. These data offer support for the inclusion of doxycycline as an alternative regimen in current IDSA recommendations. Disclosures: All authors: No reported disclosures.